Applications of pharmacogenetics in children with attention-deficit/hyperactivity disorder - Levy F (Pharmacogenomics and Personalized Medicine, 2014)
Florence Levy School of Psychiatry, University of New South Wales and Prince of Wales Hospital, Sydney, Australia Abstract: This review examines molecular genetic studies shown to be of importance in the etiology of attention-deficit/hyperactivity disorder (ADHD) and contrasts prefrontal versus subcortical mechanisms. Although these mechanisms are not completely dissociated, an understanding of prefrontal dopaminergic/noradrenergic versus subcortical D1/D2 receptor mechanisms is useful for studies of diagnosis versus potential adverse effects. Dopamine physiology, dopamine receptor studies, alpha-2 agonist studies, and dopamine transporter and potential new therapies are reviewed. Further understandings of molecular mechanisms involved in etiology versus treatment and adverse effects should help personalize the treatment of ADHD. Keywords: ADHD, dopamine transporter, dopamine receptors, alpha-2 agonists, COMT, stimulant side effects